English Trades-Union Statistics (Quarterly Journal of Economics, 1889)
English Trades-Union Statistics Get access The Quarterly Journal of Economics, Volume 3, Issue 4, July 1889, Pages 525–528, https://doi.org/10.2307/1879650 Published: 01 July 1889